QUANTIFICATION OF POLLUTION LEVELS ASSOCIATED WITH HEAVY METALS IN SHANONO AND BAGWAI ARTISANAL GOLD MINES, KANO STATE, NIGERIA - Bello, S.; Nasiru, R.; Garba, N. N.; Adeyemo, D. J. (FUDMA Journal of Sciences, 2023)
Quantification of heavy metals pollution levels in an environment is a powerful tool for converging raw heavy metals concentrations to a comprehensive level that could easily be interpreted by decision makers, managers and the public. In this work, the heavy metals concentrations were obtained using atomic absorption spectrophotometry. Element specific pollution was assessed by contamination, ecological risk, enrichment and geo-accumulation indices; Pollution load, average pollution, risk and Nemerow pollution load integrated indices were used to quantify the overall pollution level of the studied area. All the single indices computed indicated that both the soil, water and plants were polluted at different levels by all the studied heavy metals. Pollution load index, Risk index, Average pollution index and Nemerow pollution load index were estimated at 3.5, 232.0, 23.9,172.7 respectively for soils, 2.9, 964.8, 24.2, 173.1 respectively for water, 2.2, 1166.9, 14.9, 172.5 respectively for plants. These integrated indices classified the soil and water in the studied area as polluted and under strongly high ecological risk, which calls for immediate remediation measures to be implemented by appropriate authorities to at least minimize these levels
Keywords: Kano, pollution, indices, heavy metals, gold mining